PENINGKATAN KUALITAS MODUL KONTROL DALAM AKUSISI DATA DALAM SIMULASI - Tarigan, Adi Sastra Pengalaman (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
This paper describes the main advantages of this DAS module which can be made at very affordable prices and produce good performance as is commonly used in industrial control systems.In the motor control system, an alternative data acquisition system (DAS) module can use the LabVIEW interface. The DAS module is controlled by an ATmega64 AVR microcontroller which will communicate bidirectional with LabVIEW using the serial communication method. Which is used to acquire 8-bit digital input, 8-bit digital output, 8 analog input channels and also 2 analog output channels. Digital input can be used for voltages 0-5V and 0-24V. The digital output is made open collector with a "low" voltage of 0.276V. For analog input and analog output, this system has an average error of 14.47mV for the input range 1-5V; 72.34mV for the input range 0-10V; 0.037mA for the 4-20mA input range and 16.2mV for the 0-10V output range. This system is not designed for use in applications requiring real time accuracy and fast accuracy.